Gastrointestinal quality of life improves significantly after sleeve gastrectomy and roux-en-y gastric bypass: a prospective cross-sectional study within a 2-year follow-up - Nickel, Felix; Schmidt, Lukas; Bruckner, Thomas; Billeter, Adrian; Kenngott, Hannes Götz; Müller, Beat P.; Fischer, Lars (Obesity surgery, 2017)
Introduction: Morbidly obese patients have lower quality of life (QOL) when compared to the general population. So far, no studies have compared gender and procedural differences in gastrointestinal QOL after sleeve gastrectomy (SG) and Roux-en-Y gastric bypass (RYGB). Methods: Patients before and after bariatric surgery completed the gastrointestinal quality of life index (GIQLI), a 36-item questionnaire with five subscores. Differences between SG and RYGB were analyzed, as were gender differences. Results: Some 186 patients completed the questionnaire, 75 before surgery, 56 within 6 months, and 55 within 24 months after surgery. Total GIQLI score and all subscores were significantly better within 24 months after surgery (80.9 ± 19.2 vs. 109.2 ± 17.7, p < 0.001). The specific gastrointestinal items ‘feeling of fullness’, ‘eating pleasure’, ‘slow speed of eating’, and ‘diarrhea’ were also significantly better after surgery whereas many other gastrointestinal items were not different. Total GIQLI score was significantly higher for SG than for RYGB within 6 months, while there were no significant differences within 24 months after surgery. There were also no significant differences in specific gastrointestinal items between SG and RYGB within 24 months after surgery and in total GIQLI score between female and male patients.ConclusionTotal GIQLI score and all subscores were higher within 24 months after bariatric surgery. Total GIQLI score was significantly higher after SG when compared to RYGB within 6 months, but not different within 24 months after surgery. There was no difference in total GIQLI score between female and male patients.